2009
DOI: 10.1111/j.1447-0756.2009.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal arrhythmia: Prenatal diagnosis and perinatal management

Abstract: The importance of managing fetal arrhythmia has increased over the past three decades. Although most fetal arrhythmias are benign, some types cause fetal hydrops and can lead to fetal death. With the aim of improving the outcome in such cases, various studies for prenatal diagnosis and perinatal management have been published. Detailed analysis of the type of arrhythmia in utero is possible using M-mode and Doppler echocardiography. In particular, a simultaneous record of Doppler waveform at the superior venou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 46 publications
2
80
0
4
Order By: Relevance
“…Digoxin is the usual first-line drug while sotalol, flecainide and amiodarone have been used as second-line drugs. 3,4,9 In a review of published studies, out of 314 cases of foetal SVT, Krapp and colleagues reported digoxin to be significantly less effective in the treatment of SVT in foetuses with hydrops (24.6% success) as compared to foetuses without hydrops (65.4% success). 9 Another study on refractory cases of foetal tachycardia reported a success rate of 93% in the treatment of foetal SVT in hydropic foetuses using amiodarone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Digoxin is the usual first-line drug while sotalol, flecainide and amiodarone have been used as second-line drugs. 3,4,9 In a review of published studies, out of 314 cases of foetal SVT, Krapp and colleagues reported digoxin to be significantly less effective in the treatment of SVT in foetuses with hydrops (24.6% success) as compared to foetuses without hydrops (65.4% success). 9 Another study on refractory cases of foetal tachycardia reported a success rate of 93% in the treatment of foetal SVT in hydropic foetuses using amiodarone.…”
Section: Discussionmentioning
confidence: 99%
“…3 If undiagnosed and untreated, foetal tachycardia may lead to low-output cardiac failure and hydrops, thereby increasing foetal morbidity and mortality. [4][5][6] Ultrasonography can diagnose both, the abnormal foetal heart rate as well as the hydrops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[14][15][16] Los datos son limitados y aún no se han podido demostrar beneficios consistentes y reproducibles.…”
Section: Dexametasona Oral O Inmunoglobulinas Endovenosas (Igev) Paraunclassified
“…12,15,17,18 En fetos no hidrópicos la digoxina logra conversión a ritmo sinusal en el 60% de los casos; en fetos hidrópicos es necesaria la combinación con otras drogas como sotalol, la flecainida, y en menor medida la amiodarona. 12,15,[18][19][20] …”
Section: Antiarrítmicos En Taquiarritmias Fetalesunclassified